Understanding Plant Cellulose Synthases through a Comprehensive Investigation of the Cellulose Synthase Family Sequences - Carroll, Andrew; Specht, Chelsea D. (Frontiers in Plant Science, 2011)
The development of cellulose as an organizing structure in the plant cell wall was a key event in both the initial colonization and the subsequent domination of the terrestrial ecosystem by vascular plants. A wealth of experimental data has demonstrated the complicated genetic interactions required to form the large synthetic complex that synthesizes cellulose. However, these results are lacking an extensive analysis of the evolution, specialization, and regulation of the proteins that compose this complex. Here we perform an in-depth analysis of the sequences in the cellulose synthase (CesA) family. We investigate the phylogeny of the CesA family, with emphasis on evolutionary specialization. We define specialized clades and identify the class-specific regions within the CesA sequence that may explain this specialization. We investigate changes in regulation of CesAs by looking at the conservation of proposed phosphorylation sites. We investigate the conservation of sites where mutations have been documented that impair CesA function, and compare these sites to those observed in the closest cellulose synthase-like (Csl) families to better understand what regions may separate the CesAs from other Csls. Finally we identify two positions with strong conservation of the aromatic trait, but lacking conservation of amino acid identity, which may represent residues important for positioning the sugar substrate for catalysis. These analyses provide useful tools for understanding characterized mutations and post-translational modifications, and for informing further experiments to probe CesA assembly, regulation, and function through site-directed mutagenesis or domain swapping experiments.